A World Pharmacists Day 2025: Strengthening the Role of Pharmacists in the Community Through DAGUSIBU Awareness and Education: Strengthening the Role of Pharmacists in the Community Through DAGUSIBU Education - Sari Rahmadhani; Khazanah Nurain Nurdin (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
World Pharmacists Day is a strategic momentum to increase public awareness of the role of pharmacists within the healthcare system. However, public understanding of pharmacists' functions remains limited and is often confined to their role in dispensing medications. This community service activity aimed to strengthen the role of pharmacists in the community through educational and outreach programs conducted in commemoration of World Pharmacists Day. The implementation methods included the delivery of educational materials, interactive discussions, and the dissemination of information regarding the rational use of medicines and the role of pharmacists as healthcare professionals. The general public served as the primary target audience of this activity. The results demonstrated an improvement in public understanding and awareness of pharmacists' roles as providers of drug information, health counselors, and community partners in maintaining health. Furthermore, the activity enhanced public trust in pharmacists as competent and reliable sources of health information. Therefore, World Pharmacists Day can be effectively utilized as a platform for public education and for strengthening the role of pharmacists within the community.